2013
DOI: 10.1158/1078-0432.ccr-12-1542
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Inhibition Sensitizes Colon Cancer Cells to Antiangiogenic and Cytotoxic Therapy

Abstract: Purpose: Autophagy is a critical survival pathway for cancer cells under conditions of nutrient or oxygen limitation, or cell stress. As a consequence of antiangiogenic therapy, solid tumors encounter hypoxia induction and imbalances in nutrient supply. We wished to determine the role of autophagy in protection of tumor cells from the effects of antiangiogenic therapy and chemotherapy. We examined the effect of inhibiting autophagy on hypoxic colon cancer cells in vitro and on bevacizumab-and oxaliplatin-treat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(151 citation statements)
references
References 49 publications
4
147
0
Order By: Relevance
“…ATG5 expression was down regulated in 95% of CRC patients and, interestingly, increased ATG5 expression was associated with lymp hovascular invasion [92] . Other research showed that ATG5 is downregulated in colorectal carcinoma, in both tissue samples and cell lines, and that downregulation of ATG5 in CRC enhanced sensitivity to oxaliplatin [93] . Heterozygous deletion of ATG5 predisposed mice to intestinal adenoma growth and enhanced the antitumor effect of interferon gamma.…”
Section: Atg5 Genementioning
confidence: 96%
See 1 more Smart Citation
“…ATG5 expression was down regulated in 95% of CRC patients and, interestingly, increased ATG5 expression was associated with lymp hovascular invasion [92] . Other research showed that ATG5 is downregulated in colorectal carcinoma, in both tissue samples and cell lines, and that downregulation of ATG5 in CRC enhanced sensitivity to oxaliplatin [93] . Heterozygous deletion of ATG5 predisposed mice to intestinal adenoma growth and enhanced the antitumor effect of interferon gamma.…”
Section: Atg5 Genementioning
confidence: 96%
“…Furthermore, CQ inhibits phospholipase A2 and lysophospholipid acylhydrolase, enzymes that are required for the acidification of lysosomes [124] . Treating human colon carcinoma HT29 cells with CQ sensitized mouse colon cancers to antiangiogenic and cytotoxic therapy [93] . Moreover, the combination of CQ and 5FU displayed a significant advantage over treatment with 5FU alone in inhibiting tumor growth in colon 26 cells, which are a CRC cell line [125] .…”
Section: Autophagy Drugs In Crcmentioning
confidence: 99%
“…The survival of CML stem/ progenitor cells was also impaired by the depletion of ATG4B (Rothe et al, 2014). Along similar lines, the inhibition of autophagy via the administration of chloroquine (CQ, a lysosomotropic agent arresting the fusion between autophagosomes and lysosomes (Firat et al, 2012, O'Donovan et al, 2011, Sasaki et al, 2010, Selvakumaran et al, 2013) depleted the CD44 + /CD24…”
Section: Autophagy Promotes Cscs Survivalmentioning
confidence: 96%
“…6,7 A number of preclinical cancer therapy mouse xenograft models have been used to demonstrate the enhanced efficacy of cancer therapies when combined with the autophagy inhibitors chloroquine (CQ) or hydroxychloroquine (HCQ). [8][9][10] Thus, autophagy appears to be an attractive pathway to target. However, autophagy has been shown to have a protective role in a variety of organs including the gut, kidneys, and liver and combining HCQ with other drugs may exacerbate the toxicities of chemotherapy especially in these tissues.…”
Section: Introductionmentioning
confidence: 99%